2007
DOI: 10.1097/01.jnr.0000387601.24908.45
|View full text |Cite
|
Sign up to set email alerts
|

Applying the Health Belief Model to Analyze Intention to Participate in Preventive Pulmonary Tuberculosis Chest X-Ray Examinations Among Indigenous Nursing Students

Abstract: The purpose of this study was to investigate knowledge, perceptions of tuberculosis (TB) and intent to receive chest X-ray screening among indigenous (Taiwanese of ethnic Malayo-Polynesian descent) nursing students in Taiwan. A convenience sample was chosen from an technical institute in northern Taiwan that maintained admission quotas and provided scholarships for indigenous students. This school had over 150 classes and around 7,000 students, about 20%-25% of whom were ethnically indigenous. A power analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 17 publications
2
11
0
Order By: Relevance
“…Similar with Chang's study, applying the Health Belief Model to analyze intention to participate in preventive p u b l i c h e a l t h x x x ( 2 0 1 5 ) 1 e9 pulmonary tuberculosis chest X-ray examinations among indigenous nursing students, nursing students' score of general TB knowledge, perception of the benefits of TB preventive behavior, and perceived barriers are related to the adoption of behavior. 17 This study also shows that age and immigrant time are the demographic factors which should get more attention. The rates of TB preventative behavior are negatively related to the increasing age and the longer immigrant time.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Similar with Chang's study, applying the Health Belief Model to analyze intention to participate in preventive p u b l i c h e a l t h x x x ( 2 0 1 5 ) 1 e9 pulmonary tuberculosis chest X-ray examinations among indigenous nursing students, nursing students' score of general TB knowledge, perception of the benefits of TB preventive behavior, and perceived barriers are related to the adoption of behavior. 17 This study also shows that age and immigrant time are the demographic factors which should get more attention. The rates of TB preventative behavior are negatively related to the increasing age and the longer immigrant time.…”
Section: Discussionmentioning
confidence: 93%
“…Chang applied the Health Belief Model to analyze intention to participate in preventive pulmonary tuberculosis chest X-ray examinations among indigenous nursing students in Taiwan. 17 Poss studied the participation in tuberculosis screening of Mexican migrant farmworkers. 18,19 Rodríguez-Reimann investigated gender and acculturation differences in TB-specific Health Belief Model constructs, and the applicability of the HBM's traditional configuration to Mexican Americans.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have also highlighted that other educational models such as PERECEDE or health belief models have important roles in increasing the beliefs, attitude and behavior of target groups related to health ( 36 , 37 ). Furthermore, several other studies have also indicated that applying different models might be more beneficial than relying on the BASNEF model ( 36 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some research indicates that perceived threats are positively associated with healthy behaviour (Norman & Brain 2005, Chang et al. 2007).…”
Section: Discussionmentioning
confidence: 99%